2005
DOI: 10.1038/ni1155
|View full text |Cite
|
Sign up to set email alerts
|

The CDR3 regions of an immunodominant T cell receptor dictate the 'energetic landscape' of peptide-MHC recognition

Abstract: The energetic bases of T cell recognition are unclear. Here, we studied the 'energetic landscape' of peptide-major histocompatibility complex (pMHC) recognition by an immunodominant alphabeta T cell receptor (TCR). We quantified and evaluated the effect of natural and systematic substitutions in the complementarity-determining region (CDR) loops on ligand binding in the context of the structural detail of each component of the immunodominant TCR-pMHC complex. The CDR1 and CDR2 loops contributed minimal energy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
138
1

Year Published

2006
2006
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 171 publications
(155 citation statements)
references
References 56 publications
12
138
1
Order By: Relevance
“…Whereas the TCR-MHC contacts are typically extensive, binding studies have shown that these interactions are governed by "energetic hotspots" (10,11). Consistent with this finding, our analyses showed that three (65, 69, and 155) positions, on the MHC were invariably contacted in essentially all TCR-pMHC-I systems reported to date (14).…”
Section: Discussionsupporting
confidence: 78%
See 3 more Smart Citations
“…Whereas the TCR-MHC contacts are typically extensive, binding studies have shown that these interactions are governed by "energetic hotspots" (10,11). Consistent with this finding, our analyses showed that three (65, 69, and 155) positions, on the MHC were invariably contacted in essentially all TCR-pMHC-I systems reported to date (14).…”
Section: Discussionsupporting
confidence: 78%
“…Namely, the current TCR-pMHC-I structural database demonstrates that the germline-encoded CDR1/2 loops frequently play an important role in contacting the peptide, but perhaps more critically, the CDR3 loops can and do play a principal role in contacting the MHC-I. This interpretation is further supported by mutagenesis experiments that demonstrated an important energetic role for the CDR3 loops in contacting the MHC-I and for the CDR1/2 loops in contacting the peptide (8,11).…”
Section: Discussionsupporting
confidence: 60%
See 2 more Smart Citations
“…Gene rearrangement of different V, D, J and C regions leads to the assembly of highly diverse receptors with varying lengths. 21 An increased proportion of T cells with a restricted CDR-3 TCR-Vb nucleotide length, which is representative of clonal T-cell expansion, is known as 'TCR-Vb-repertoire skewing'. [22][23][24][25] In normal T-cell homeostasis, a limited number of clones undergo periodic expansion in response to foreign antigens.…”
Section: Introductionmentioning
confidence: 99%